Development of a Web-Based Youth Innovation Village System Using Laravel Framework: Author's Country: Indonesia (Information System; Universitas Buana Perjuangan Karawang, 2025)
Youth play a crucial role in social development and serve as agents of change contributing to national progress. Karang Taruna, as a youth organization, has a strategic role in enhancing social welfare, including in Mekarjati Village. Since its establishment on November 10, 2013, Karang Taruna Mekarjati has grown with 13 subunits in each neighborhood unit (RW), serving a community of 11,881 people. However, the organization's business processes, such as member registration, social activity management, leadership training, and the formation and monitoring of MSMEs or startups, are still conducted manually. This results in operational inefficiencies and increases the risk of administrative errors. This study aims to design and develop a web-based system called